The effect of dividend policies on wealth maximization – a study of some selected plcs - C.N. Ozuomba; A.S. Anichebe; P.V.C. Okoye (Cogent Business & Management, 2016)
This research article examines how share value thus shareholders wealth is affected by dividend policies. This study seeks to analyze the effect of firm’s dividend policies on shareholders’ value of public companies in Nigeria, to empirically examine the linkage of dividend payout with information asymmetry, and to analyze the effect of various dividend policies on shareholders wealth. This study is based on survey design covers a one-year period with a sample of 10 quoted companies in the Nigeria stock exchange. In so doing, the methodology adopted is the Anova. This study shows the relevance of dividend and further proves that dividend policies of public limited companies influence the wealth of shareholders in Nigeria.